Upaya Wanita Usia Subur Dalam Mencegah Permasalahan Kesehatan Reproduksi Di Wilayah Kerja Puskesmas Kalibagor Kabupaten Banyumas - Mu'minah, Ikhwah; Purwo Aniarti, Reni; Atmarina Yuliani, Diah (INVOLUSI: Jurnal Ilmu Kebidanan, 2023)
Reproductive health is an important issue to get attention. It should be realized that reproductive health cannot be separated from health in general, so efforts to maintain healthy conditions in terms of reproductive health must be supported by knowledge and behavior of clean and healthy living. Women have a reproductive system that is very vulnerable to disturbances that can cause problems for their reproductive health. The type of research used in this research is quantitative research with a descriptive approach. The research respondents were selected based on certain predetermined criteria or objectives. The sampling technique is purposive sampling, which is a sampling technique based on certain criteria. The results of the research on the efforts of women of childbearing age to prevent reproductive health problems are carried out in ways such as breastfeeding for 2 years, using underwear made of cotton, using pads during menstruation, not sharing underwear with other people, early detection of breast cancer by conscious and conscious examination and early detection of cervical cancer by means of IVA examination, faithfulness to partners and not taking drugs, not smoking and not consuming alcohol